Kajian terhadap tafsir rawa’i al-bayan: Tafsir ayat al-ahkam min al- quran muhammad ali ash-shabuni - Laila Badriyah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
Ali Ash-Shobuni including mufassir productive scholars of this century and has many prolific phenomenal. One of them is Rawa'i al Bayan. Book revealed about the legal verses in al-qura'an. Any discussion of the theme of law in accordance with the content of paragraph. Systematics used in rawa'i al-bayan is systematic modern thematic plural. A presentation of a model in which there are many important theme that is based on the construction standards Manuscripts. Ali Ash-Shobuni convey firmly and investigated the wisdom behind al-Baqarah verse 222-223 of "Wife Menjahui Time Periods".